'I never did anything wrong' – Trojan Horse: a qualitative study uncovering the impact in Birmingham. Issue 2 (17th February 2018) - Awan, Imran
Abstract: In 2014, the city of Birmingham (UK) became embroiled in a high-profile scandal that would bring it and the wider education system under disrepute. The 'Trojan Horse' affair, as it become known, began with an anonymised letter that claimed hard-line 'Islamists' were plotting and planning to take over a number of schools in Birmingham. Amongst the allegations were that some of the schools had been promoting gender segregation and that children were not safeguarded against the risks of extremism. This article examines some of those issues in relation to the Trojan Horse scandal and uses a qualitative study focused on participants from the area of Birmingham. As the tribunal hearings against the teachers have now found no wrongdoing, the findings reported in this article suggest that Muslim communities feel unfairly categorised as extremists and that such issues have impacted upon their sense of identity and belonging.